Hospital Management System Human Resource 1 (New Hire on Board and Employee Self Service, Performance Management, Recruitment and Applicant Management, Social Recognition, Competency Management: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Hospital Management System Human Resource 1 is a web-based system that automatesand streamlines HR activities, including onboarding, recruiting, hiring, monitoring, andrecognizing employee performance. The traditional way of using email for communication canbe time-consuming and ineffective, leading to poor security measures and data loss, whichcan impact the daily operations of business. To address this issue, the project team developeda secure web-based system that simplifies the onboarding process and enables HRmanagers to track newly hired employees with ease. The system has enhanced securitymeasures to ensure the protection of HR 1 data, eliminating the need for complex andpaperwork-heavy processes. The system is designed to manage the version of HR 1 In HMSactivities and aims to make managing HR 1 less challenging for businesses.By breaking the project into manageable sprints and prioritizing tasks based on feedback, theteam delivered a web-based system that efficiently handles HR transactions for a hospital.This involved collaboration with HR personnel and stakeholders, quick delivery of a workingsystem, and ongoing improvement. Then, the team determines the most effective way toaddress the issues and improve the Hospital Management System Human Resource 1.The project aimed to improve Hospital Management System Human Resource 1 by reducingpaperwork, saving time, and ensuring data security while staffing the hospital effectively. Theteam developed a web-based system that efficiently monitors newly hired employees andproduces timely HMS HR 1 reports with minimal effort.
Keywords: IT & Management